Korelasi Rambut Berwarna dengan Stigma Kecantikan Perempuan Urban : Studi Kasus Kota Semarang - Ulfah, Nisa Alif (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This study aims to analyze the correlation between colored hair and beauty stigma faced by urban women in Semarang City using Erving Goffman's social stigma theory. The research employs a qualitative method with a phenomenological approach, collecting data through in-depth interviews with two female participants who frequently dye their hair. The findings reveal that women with colored hair encounter various forms of social stigma, including physical stigma, character stigma, and group stigma. Colored hair is perceived as deviating from traditional beauty norms that idealize long, straight black hair, leading to verbal harassment, disapproving looks, and discrimination in the workplace. However, these women develop strategies to manage this stigma, such as hiding their hair color with wigs or adjusting their hair color to fit social contexts. Additionally, self-acceptance and confidence are crucial in facing social stigma. This study highlights the complex dynamics between social norms and self-expression in an urban context and underscores the importance of education and increased social awareness to reduce negative stigma associated with colored hair.